PENGARUH MEREK TERHADAP PERILAKU KONSUMEN PADA PT.FASTGLOBAL BERKAH MANDIRI - Munir Azhari (Sekolah Tinggi Manajemen IMMI Jakarta, 2022)
The Brand influence on consumer behavior at PT. Fastglobal Berkah Mandiri, Munir Azhari, STIMA IMMI, 2022. consumer behavior is a crucial part of marketing to study. consumer behavior is influenced by various factors, one of which is the brand. The brand phenomenon in delivery services is interesting to research and study, not only for researchers but also for businesses, especially delivery service businesses. The purpose of this research, among others, is that the writer wants to know whether there is a brand influence on consumer behavior and how much influence the brand has on consumer behavior. This study discusses the brand variable as the independent variable (X) and consumer behavior as the dependent variable (Y). This research uses quantitative research methods. Simple linear regression equation Y=7.187 – 0.879x. The value of the regression coefficient (b) can be interpreted that every 1 unit increase in the value of a given brand will cause an increase of 1 unit value of consumer behavior by 0.879. Value of r = 0.930. then the correlation coefficient is r = 1 or close to 1 so that it has a very strong relationship or correlation between brand variables (X) and consumer behavior (Y). KP = 0.9302 X 100% = 86.5%. So it is known that the brand contribution to consumer behavior is 86.5% and the remaining 13.5% is influenced by other factors. Tcount value obtained 18.966 and Ttable 2.00324. So that Tcount Ttable, that is 18.966 2.00324. Therefore Ho is rejected and Ha is accepted, meaning that there is a strong positive (significant) relationship between brands and consumer behavior at PT. Fastglobal Blessings Mandiri.